Deliberative Politics towards of The Government Policy in West Kalimantan Indonesia - Martoyo; Elyta; Herlan; Sujendra, Bima (Technium Social Sciences Journal, 2021)
In a representative democracy system, the political concept of deliberation can be realized directly through the deliberation process and the election of people’s representatives, including preparing the District Government Annual Work Plan. This study aims to analyze the community participation in providing information about conditions, needs, and attitudes in the preparation of District Government Annual Work Plan Sekadau Regency West Kalimantan Province In 2019. This research uses the qualitative method. The data was collected by interview, observation, and documentation study techniques. Based on the research results that have been done, it was found that the community has responded well to the drafting of the District Government Annual Work Plan. However, the organization could not see whether they had read the map or not, and the community has not seen its priority programs. The recommendation from this research is that the Sekadau Regency Government offers a particular proposal and keeps socialized to increase community participation to increase from year to year.